Evaluasi Simpangan Pada Bangunan Bertingkat Beton Bertulang berdasarkan Analisis Pushover dengan Metode ATC-40 - Zebua, Dermawan; Wibowo, Leonardus Setia Budi; Cahyono, M. Shofwan Donny; Ray, Norman (Universitas Dr. Soetomo, 2020)
Indonesia is an area prone to earthquakes. Earthquakes caused by the movement of the earth's plates are the biggest cause of earthquakes that will cause damage to the building structure. Earthquakes occurring in Indonesia often cost lives. However, it is certain that the cause of the loss of life is not directly caused by the earthquake, but caused by the destruction of the building that caused the collapse in the building.The purpose of writing the research is to determine the performance criteria of the university building's seismic performance from the performance point value using the ATC-40 code, showing the melamine scheme (plastic joint distribution) occurring from the calculation of the software program, knowing the collapse pattern of the building so it can be known the joints Suffered damage and suffered destruction of pushover analysis.From the results of the study, the structure of the building is able to provide nonlinear behavior indicated by the initial phase and the majority of plastic joints occur in new beam elements and then column elements. The performance level of the structure enters the criterion of operational which means that minor structural and building damage can be reused immediately.